New Zealand Journal of Forestry Science - Falshaw, Ruth
The New Zealand Journal of Forestry Science is an international journal covering the breadth of forestry science. While planted forests are a particular focus, manuscripts on a wide range of forestry topics (including tropical species, climate change, and policy) will also be considered. Forestry species are those capable of reaching at least five metres in height at maturity in the place they are located, but not grown or managed primarily for fruit or nut production. Original articles must report on a completed piece of substantial research that is relevant to an international audience. In all cases, a hypothesis must be presented and results must be sound without errors of fact, logic, interpretation, or calculation. Key details must be provided for all methods used. The correct statistical tests must be applied, where appropriate. Discussion must be logical and comprehensive, yet concise. Any conclusions must be justified and supported by the data presented. Short notes, subject reviews and book reviews will also be considered if they are within the scope of the journal. Conference papers may be acceptable if they are part of a set of proceedings being published by the journal.